Central venous oxygen saturation changes as a reliable predictor of the change of CI in septic shock: To explore potential influencing factors - Ran An; Xi-Xi Wan; Yan Chen; Run Dong; Chun-Yao Wang; Wei Jiang; Li Weng; Bin Du (Chinese Journal of Traumatology)
Purpose: Assessing fluid responsiveness relying on central venous oxygen saturation (ScvO2) yields varied outcomes across several studies. This study aimed to determine the ability of the change in ScvO2 (ΔScvO2) to detect fluid responsiveness in ventilated septic shock patients and potential influencing factors. Methods: In this prospective, single-center study, all patients conducted from February 2023 to January 2024 received fluid challenge. Oxygen consumption was measured by indirect calorimetry, and fluid responsiveness was defined as an increase in cardiac index (CI) ≥ 10% measured by transthoracic echocardiography. Multivariate linear regression analysis was conducted to evaluate the impact of oxygen consumption, arterial oxygen saturation, CI, and hemoglobin on ScvO2 and its change before and after fluid challenge. The Shapiro-Wilk test was used for the normality of continuous data. Data comparison between fluid responders and non-responders was conducted using a two-tailed Student t-test, Mann Whitney U test, and Chi-square test. Paired t-tests were used for normally distributed data, while the Wilcoxon signed-rank test was used for skewed data, to compare data before and after fluid challenge. Results: Among 49 patients (31 men, aged (59 ± 18) years), 27 were responders. The patients had an acute physiology and chronic health evaluation II score of 24 ± 8, a sequential organ failure assessment score of 11 ± 4, and a blood lactate level of (3.2 ± 3.1) mmol/L at enrollment. After the fluid challenge, the ΔScvO2 (mmHg) in the responders was greater than that in the non-responders (4 ± 6 vs. 1 ± 3, p = 0.019). Multivariate linear regression analysis suggested that CI was the only independent influencing factor of ScvO2, with R2 = 0.063, p = 0.008. After the fluid challenge, the change in CI became the only contributing factor to ΔScvO2 (R2 = 0.245, p < 0.001). ΔScvO2 had a good discriminatory ability for the responders and non-responders with a threshold of 4.4% (area under the curve = 0.732, p = 0.006). Conclusion: ΔScvO2 served as a reliable surrogate marker for ΔCI and could be utilized to assess fluid responsiveness, given that the change in CI was the sole contributing factor to the ΔScvO2. In stable hemoglobin conditions, the absolute value of ScvO2 could serve as a monitoring indicator for adequate oxygen delivery independent of oxygen consumption.